FEATURES OF COLONIZATION OF THE MICROFLORA OF THE ORAL CAVITY AND INTESTINES IN PREMATURE INFANTS WITH NECROTIZING ENTEROCOLITIS WHO UNDERWENT SURGICAL TREATMENT - Musayev, A.A. (World of Medicine and Biology, 2025)
The microflora of the oral cavity and feces in the first 7 days of life was studied in 20 premature infants with necrotizing enterocolitis undergoing surgical treatment (the main group) and in 20 premature infants without necrotizing enterocolitis (the control group). In 10 % of the children of the main group and in 95 % of the control group, the microflora was normal. In both groups, Bacteroides spp dominated the microflora in 58 %. and the number of other gram-negative aerobic bacteria, including E. coli, gradually increased, while colonization by gram-positive bacteria was slower. Clostridium spp. They were present in only 10 % of the children of the main group. In the first 4 days of birth, the incidence of C. butyricum, C. perfringens, and C. dificile in the main group ranged from 3 to 7 % with a gradual tendency to increase colonies. The colonization pattern of the oral cavity and colon in premature infants with necrotizing enterocolitis differs significantly from newborn premature infants without necrotizing enterocolitis.